Shortages Under Free Prices : The Case of Ukraine in 1992 - Lane, Timothy (IMF Working Papers; Working Paper, 1994)
This paper examines the coexistence of free prices and shortages for a range of consumer goods in Ukraine during 1992. Enterprises making consumer goods were substantially free to set market-clearing prices. Yet, Ukraine's official consumer market experienced continued shortages, while the same goods traded at higher prices in parallel markets. The paper advances a model of enterprise behavior in an environment of central allocation of inputs at preferential prices. We show that central allocation of key inputs according to perceived 'need' creates incentives for excess demand to be perpetuated despite formal price liberalization. The analysis brings forth the importance of abolishing allocation mechanisms for price liberalization to bring its full efficiency effects.